PETA GERAKAN SYIâAH DI KALIMANTAN SELATAN - humaidy, Humaidy (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
This article traces back the entry of the Shiâa in South Kalimantan through the inclusion of Islamic Wujudiyah (panentheism) Sufismwhich was firstspreadin the kingdom of Banjar. Â This isdue to the similaritybetween Wujudiyah Sufism with the concept of Irfan in Shia. However, the influence of Shia in Â South KalimantanÂ suffered a setback atthe era Â of Syekh Muhammad al-Banjari Arsyad (1710-1812 AD). Â According to Habib Ali,Shia began to revive in South Kalimantan after the Iranian revolution in 1979. Â Jaâfari school of thought (madhabs)Â is the growing Shiah in South Kalimantan. The Developmentof Shiâa in South kalimantan faces manychallenges since Muslims in South Kalimantan have a strong belief in Sunni